INVESTIGATIONS ON STRENGTH ANALYSIS OF LAP JOINTS FOR ALUMINUM- EPOXY COMPOSITE PLATES USING FINITE ELEMENT METHOD WITH EXPERIMENTAL VERIFICATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this dissertation, the mechanical behaviour of 2-bolted single-lap Aluminum glassfiber composite plate with high strength bolts is investigated, both analytically and experimentally. A detailed 3D non-linear FE model of composite bolted joints has been developed. The model replicates with good agreement the experimental tensile tests up to the point where bearing damage occurs and reproduces the joint behaviour correctly. The evolution of contact during the test is studied showing a correlation with the joint stiffness. Using the developed FE model, the distribution of the stress components around the holes of the composite joints is studied together with the effects of hole clearance and position of bolts. The stress along the fibres is identified as the critical stress component and the compressive fibre failure of the 0° oriented plies as the start of the bearing damage. The 0° oriented plies in the cylindrical part of the hole are found to be the plies carrying the bearing load. Increasing clearance reduces the extent of the bolt shank-hole contact and leads to higher stresses and lower joint stiffness. The 45° and -45° oriented plies are found to have a key role in the joint bearing strength and shear-out failure.